2006
DOI: 10.1186/1479-5868-3-19
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Many youth today are physically inactive. Recent attention linking the physical or built environment to physical activity in adults suggests an investigation into the relationship between the built environment and physical activity in children could guide appropriate intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
313
4
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(372 citation statements)
references
References 50 publications
32
313
4
4
Order By: Relevance
“…It is highly possible that these counties are mostly located in the semiarid and desert area with a lack of trees and green spaces, and thus tree canopy coverage may work more than expected to decrease LTPI. This finding also supports the empirical evidence of negative associations between tree canopy and LTPI in previous research [90][91][92]. On the other hand, tree canopy coverage (β 3 ) in 6% of the counties has a positive association, and in 60% of the counties, it is not associated with LTPI, which does not correspond to the expected association.…”
Section: Discussionsupporting
confidence: 88%
“…It is highly possible that these counties are mostly located in the semiarid and desert area with a lack of trees and green spaces, and thus tree canopy coverage may work more than expected to decrease LTPI. This finding also supports the empirical evidence of negative associations between tree canopy and LTPI in previous research [90][91][92]. On the other hand, tree canopy coverage (β 3 ) in 6% of the counties has a positive association, and in 60% of the counties, it is not associated with LTPI, which does not correspond to the expected association.…”
Section: Discussionsupporting
confidence: 88%
“…(47) The social ecological model (29, 42) suggests that factors at multiple levels (e.g. individual, social, environmental) influence PA behavior, and research indicates that the neighborhood environment may be an important setting for increasing children’s PA.(13, 26) In addition to the influence of neighborhood, other social and behavioral factors (e.g., parent support and outdoor PA) may play an important role with regard to children’s MVPA. (36, 37)…”
Section: Introductionmentioning
confidence: 99%
“…54,56,57 Evidence suggests parks and other outdoor recreation sites are second only to schools as the setting where children and youth are most active, 58,59 and numerous studies have shown higher physical activity levels among children and youth living near parks or recreation centers. [57][58][59][60][61] According to the 2011-12 NSCH, 22 the large majority of American children and youth report living in neighborhoods with at least 1 park or playground area. However, significant disparities exist by ethnicity and socioeconomic status, earning the U.S. a B-.…”
Section: Community and Built Environmentmentioning
confidence: 99%